Accident Studies and Road Safety Audit of Four Lane Jammu to Udhampur Section of NH-1A From Km 15.200 To Km 67.000 of NH 1-A In The State of Jammu & Kashmir - Sharma, Lovepreet (My University, 2017)
Road Safety Audit (RSA) is a formal procedure for assessing accident potential and safety performance of new and existing roads. Road safety audit is an efficient, cost effective and proactive approach for the improvement of road infrastructure. It has been proved that road safety audit has the potential to save lives. It is applicable at all stages of project implementation i.e. from planning stage to developing stage, detailed design, construction stage, operation and maintenance stage. Road Safety Audit is very important for the proper implementation, design, operation and maintenance for the design period of the project highway. It is very important from the safety aspects of road as well as road user. It means safer roads which means safer life. This study deals with the collection and analysis of accident data for year 2016 of existing four lane National Highway 1 A for Jammu- Udhampur, so as to identify the areas of major concern, including black spots, accident-prone stretches on the project highway. It also involves the determination of accident severity index and rate per million of entering vehicles on the project highway. The value of Average severity index is used to calculate blackspots and the value of rate per million of entering vehicles is to calculate the number of crashes occurring at a particular location. This study also deals with the road safety review of existing four lane highway and providing various recommendations for various deficiencies that exist on the project highway. It also includes the development phase audit which involves plan and profile data checking for the four-lane highway as per IRC specifications for the safe design of horizontal and vertical curves. It provides various checklists for development phase audit from the safety aspects which is prepared as per latest MORTH specifications.
Master of Engineering -Civil Infrastructure
Keywords: Road Safety Audit; Accident Analysis; Geometric Design